The pseudosymmetric crystal structure of 3-((1R,2S)-1-methylpyrrolidin-1-ium-2-yl)pyridin-1-ium hexachloridostannate(IV), C10H16N2SnCl6 - Wolke Marie Barbara; Reiss Guido J. (Zeitschrift für Kristallographie - New Crystal Structures)
C10H16N2SnCl6, monoclinic, I2 (no. 5), a = 14.0477(4) Å, b = 8.9140(2) Å, c = 27.6199(6) Å, β = 93.060(2)°, Z = 8, V = 3453.67(15) Å3, R gt(F) = 0.0395, wR ref = 0.0858, T = 290 K.